Compliance on safety behaviour among police officers in Royal Malaysia Police (RMP) - Norhidaya, Mohamad Othman (2017)
Very few studies focusing on safety behaviour among police officer in Malaysia have been conducted. Thus, this study was an attempt to determine the impacts of certain factors on safety behaviour compliance among police officers in Royal Malaysia Police (RMP) in particular those who are directly involved with operational task. The focus of this study was to examine the influence of job safety, co-worker safety, supervisor safety, management safety and satisfaction of safety programme/policies, on safety behaviour compliance among the RMP officers. This quantitative study utilized the five facets of Work Safety Scale (WSS) (Hayes et al., 1998) questionnaire to measure perceptions on safety at work. 178 police officers from the Kuala Lumpur Police District were included in this study. The findings showed that co-worker safety supervisor safety management safety and safety programme were significantly related to compliance on safety behaviour. However, job safety is not significantly related to safety behaviour. Recommendations and suggestion for future study were also discussed.